Cortisol, testosterone, and insulin action during intense swimming training in humans - Tyndall, G. L.; Kobe, R. W.; Houmard, J. A. (European Journal of Applied Physiology, 1996)
An increase in the amounts of circulating plasma cortisol or a decrease in testosterone can result in whole-body insulin resistance. The purpose of this study was to determine if the increase in cortisol and/or decrease in testosterone concentrations commonly evident with intense endurance training is associated with insulin resistance. Male (n = 9) and female (n = 10) swimmers were examined during the off-season, after 9 weeks (9 WKS) of training averaging 5,500 m* day(-1) and after an additional 9 weeks (18 WKS) of training averaging 8,300 m*day(-1). Resting plasma cortisol concentration was (P < or = 0.05) higher in the women compared to the men at 9 WKS; values were not significantly different between genders at 18 WKS. Plasma testosterone concentration decreased significantly (P < or = 0.05) in the men at 9 and 18 WKS, but did not change in the women. Whole-body insulin action, as determined by insulin and glucose responses during a 120 min, 75-g oral glucose tolerance test, did not change with training in either the men or women. These data indicated that plasma testosterone concentration can decrease in male swimmers during intense endurance training; this alteration does not affect wholebody insulin action. There would also appear to be a gender-specific response of plasma cortisol to endurance training, which does not influence insulin action.